Metabolism of Odontoblast-like cells submitted to transdentinal irradiation with blue and red LED - Dantas de Almeida, Leopoldina de Fatima; Basso, Fernanda Goncalves [UNESP]; Silveira Turrioni, Ana Paula; de-Souza-Costa, Carlos Alberto [UNESP]; Hebling, Josimeri [UNESP] (Elsevier B.V., 2017)
Objectives: The present study evaluated the trans-dentinal effect of light emitting diodes (LEDs) irradiation on the metabolism of odontoblast-like cells. Methods: Seventy-two dentin discs (0.2 mm thick) were obtained from human molar teeth. MDPC-23 cells (20,000 cells/disc) were seeded on the pulpal side of the discs using DMEM, supplemented with 10% fetal bovine serum (FBS). After 12 h, the culture medium was replaced with DMEM containing 0.5% FBS. After additional 12 h, blue (455 +/- 10 nm) or red (630 +/- 10 nm) LEDs were used at irradiances of 80 and 40 mW/cm(2), respectively, to irradiate the occlusal side of the discs. The energy doses were fixed at 2 or 4 J/cm(2). Cell viability, alkaline phosphatase activity (ALP), total protein production and collagen synthesis were evaluated 72 h after irradiation. Data were submitted to Kruskal-Wallis and Mann-Whitney tests (alpha = 0.05). Results: Red light promoted proliferative effects at the energy dose of 4 J/cm(2) Conversely, cell cultures irradiated with 2 J/cm(2) emitted by the blue light showed reduced viability. ALP production was stimulated by red light in comparison with blue light at 4 J/cm(2). Total protein production was reduced after exposure to blue light at 4 J/cm(2), while no effect was observed on collagen production. Conclusions: Irradiation with red LED at 4 J/cm(2) bio-stimulated the viability of odontoblast-like cells, whilst blue light had unfavorable effects on the cellular metabolism.
Keywords: phototerapy; light emitting diodes; odontoblasts; dentin; dental pulp